2021
DOI: 10.1002/chem.202102472
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Propelling Hybrid Gels Incorporating an Active Self‐Assembled, Low‐Molecular‐Weight Gelator

Abstract: Hybrid gel beads based on combining a low‐molecular‐weight gelator (LMWG) with a polymer gelator (PG) demonstrate an enhanced ability to self‐propel in water, with the LMWG playing an active role. Hybrid gel beads were loaded with ethanol and shown to move in water owing to the Marangoni effect changes in surface tension caused by the expulsion of ethanol – smaller beads move farther and faster than larger beads. Flat shapes of the hybrid gel were cut using a “stamp” – circles moved the furthest, whereas stars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…The characterization of the gel beads in this work is consistent with our previous report, which made use of this type of bead in a different context . The formulation employed 0.3% wt/vol of the DBS-CONHNH 2 LMWG and 1.0% wt/vol of the agarose PG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the gel beads in this work is consistent with our previous report, which made use of this type of bead in a different context . The formulation employed 0.3% wt/vol of the DBS-CONHNH 2 LMWG and 1.0% wt/vol of the agarose PG.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid PG/LMWG gel systems open the possibility of imposing shape/morphology on gels, such as beads. , For the work in this paper, we envisioned that the use of agarose as a PG, and employing a higher concentration compared to our previous gel blocks, might facilitate the formation of well-defined beads and prevent the mechanical degradation caused by stirring without compromising the activity of our catalyst. Using catalyst-loaded beads allows for facile precise dosing of Pd compared to using gel blocks since each bead contains a discrete, known amount of Pd.…”
Section: Introductionmentioning
confidence: 99%
“…Initially DBS-CONHNH 2 /GG gel beads were prepared by the emulsion method previously described by us, 14 with CaCl 2 being used for crosslinking (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). 14 We have demonstrated that in such hybrid gels, the LMWGs provided functionality, whilst the alginate offered mechanical support and robustness to shape and structure the LMWGs into gel beads or tubes. On starting this work with gellan gum, we wanted to explore the potential use of this PG instead of calcium alginate to develop gels with enhanced properties.…”
Section: Introductionmentioning
confidence: 93%
“…In this regard, we recently explored multicomponent hybrid gels based on the LMWG 1,3:2:4-di­(4-acylhydrazide)-benzylidene sorbitol (DBS-CONHNH 2 ; Scheme ) and the polysaccharide calcium alginate (Scheme ). DBS-CONHNH 2 is a thermally triggered LMWG that self-assembles in response to heat–cool cycles, giving biocompatible hydrogels that have been employed in a variety of ways including drug delivery, cell culture, and environmental remediation. The biopolymer alginate forms hydrogels when cross-linked with bivalent cations (e.g., Ca 2+ from CaCl 2 ). Combining the two gelators allowed us to impose a spherical shape on the LMWG while keeping its functionality, leading to a rare example of LMWG hydrogel beads. , …”
Section: Introductionmentioning
confidence: 99%